Pengaruh DER, NPM dan Free Cash Flow Terhadap Kebijakan Dividen Bank Syariah di Indonesia - Nulhakim, Irvan; Hardiansyah, Hardiansyah; Khatimah, Husnul (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to examine the factors influencing dividend policy in Islamic banks listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. A quantitative approach was employed in this research. The independent variables selected include the debt-to-equity ratio (X1), net profit margin (X2), and free cash flow (X3), while the dependent variable is the dividend policy. Secondary data was utilized, and the sample consisted of all Islamic banks listed on the Indonesia Stock Exchange. The findings reveal that the debt-to-equity ratio and free cash flow have a positive and significant effect on dividend policy, with t-statistcs is 4,30 and 3,76, whereas the net profit margin has no significant effect. Simultaneously, all independent variables in this study exhibit a positive and significant impact on dividend policy, f-statistics is 38,10. The results of this research are expected to serve as a valuable reference for stakeholders in Islamic banks and future studies related to dividend policy.